Impact of muscular symptoms and/or pain on disease characteristics, disability, and quality of life in adult patients with hypophosphatasia: A cross-sectional analysis from the Global HPP Registry - Dahir, Kathryn M.; Kishnani, Priya S.; Martos-Moreno, Gabriel Ángel; Linglart, Agnès; Petryk, Anna; Rockman-Greenberg, Cheryl; Martel, Samantha E.; Ozono, Keiichi; Högler, Wolfgang; Seefried, Lothar (Frontiers in Endocrinology, 2023)
Introduction: Hypophosphatasia (HPP) manifests in adults as fractures/pseudofractures, pain, muscle weakness, and other functional impairments. Better phenotypic disease characterization is needed to help recognize disability and treat patients with HPP. Methods: Baseline/pretreatment demographic, clinical characteristic, and patient-reported disability/health-related quality-of-life (HRQoL) data from adults (≥18 y) in the Global HPP Registry (NCT02306720) were stratified by presence of overt skeletal manifestations (skeletal group) versus muscular/pain manifestations without skeletal manifestations (muscular/pain group) and summarized descriptively. Disability was measured using the Health Assessment Questionnaire–Disability Index (HAQ-DI), and HRQoL using the 36-item Short Form Health Survey (SF-36v2). Results: Of 468 adults, 300 were classified into the skeletal group and 73 into the muscular/pain group. The skeletal group had a higher median age at baseline (50.1 vs 44.4 y; P=0.047) but a lower median age at first HPP manifestation (12.3 vs 22.1 y; P=0.0473), with more signs and symptoms (median, 4 vs 3; P<0.0001) and involved body systems (median, 3 vs 2; P<0.0001) than the muscular/pain group. More patients in the skeletal group required any use of mobility aids (22.6% vs 3.5%, respectively; P=0.001). Six-Minute Walk test distances walked were similar between groups. SF-36v2 and HAQ-DI scores were similar between groups for physical component summary (n=238; mean [SD]: 40.2 [11.0] vs 43.6 [11.2]; P=0.056), mental component summary (n=238; mean [SD]: 43.6 [11.3] vs 43.8 [11.8]; P=0.902), and HAQ-DI (n=239; median [minimum, maximum]: 0.4 [0.0, 2.7] vs 0.3 [0.0, 2.1]; P=0.22). Conclusions: Adults with HPP experience similar QoL impairment regardless of skeletal involvement.